The impact of the covid-19 pandemic on the efficiency performance of Islamic Banks in Indonesia: A two-stage data envelopment analysis approach - Marlina, Lina; Saepulloh, Asep; Dewi, Sinta Verawati (Universitas Negeri Surabaya, 2024)
Additionally, resilience to crises makes Islamic banking one of the leading solutions to overcoming the economic crisis. This research aims to analyse the level of performance of Islamic banking in Indonesia and determine factors, including the impact of the COVID-19 pandemic during the 2011-2022 period, using 11 Islamic commercial banks in Indonesia. The analysis method used is DEA Two Stage, with secondary data from the financial reports of each Islamic commercial bank. The input variables are fixed assets, labour costs, and third-party funds. The output variables are the amount of financing provided and operational income. The research results explain that no Islamic commercial banks in Indonesia achieved optimal efficiency during the research period. Then, the efficiency level of Islamic commercial banks in Indonesia fluctuated yearly during the research period. Furthermore, the COVID-19 pandemic has impacted the efficiency level of Islamic commercial banks in Indonesia. In the potential improvement analysis, know that the most significant source of inefficiency is the output variable: the amount of financing provided. The results of the benchmarking analysis found Islamic commercial banks with the most references, where the year most referred to was 2021-2022.